Fenomena Pinjaman Online di Masyarakat: Studi Empiris di Kalangan Santri Mahasiswa - Muhammad Afifudin; M. Fuad Hadziq; Rini Febrianti; Muhamad Komarudin (Universitas Sains dan Teknologi Komputer, 2024)
Islamic boarding schools are educational institutions that are free from credit or financing practices. Islamic boarding schools are free from online loans, currently many santri are trapped in online loans. The purpose of this study is to analyze in depth the santri who have online loans, the reasons for making online loans, and how to pay off these loans. This research uses a descriptive qualitative approach based on the phenomenon with the aim of obtaining sample data results in the field. Comprehensive surveys and interviews were conducted with santri who have online loans at boarding schools. The sample consisted of 40 santri and, we conducted the data collection using a semi-structured questionnaire. The results of this study show that most santri can obtain online loans and each santri uses online loans for consumptive needs and not for productive needs, thus having a negative effect on the educational process at boarding school.